External evaluation: National Vocational Qualifications System project - Katherine Caves; Ursula Renold (ETH Zurich, KOF Swiss Economic Institute, 2019)
The NVQS project began in 2015, running in three phases through 2023. The project's overall goal is to contribute to building a sustainable system of national vocational qualifications in Nepal. This work should lead to three primary outcomes: a Nepal Vocational Qualifications System (NVQS), including a National Vocational Qualifications Framework (NVQF), and National Vocational Qualifications Authority (NVQA). National Qualifications Frameworks (NQFs) are a global phenomenon intended to help drive transparency, permeability, quality, and employer engagement in education (CEDEFOP, 2010). The purpose of this external evaluation (EE) is to support the design of the NVQS project's future by reflecting on the Phase 1 achievements of the NVQS, interviewing key stakeholders, and bringing a long-term perspective to bear on the project's goals and possibilities. The self-valuation (SE), completed in May of 2018, reports extensively and thoroughly on the activities and operational achievements of the project in its first three years. This EE finds that the project has had a successful first phase, needs minor revision, and can build on its challenges
Keywords: 330